2022
DOI: 10.1111/jocn.16280
|View full text |Cite
|
Sign up to set email alerts
|

Commitment, perception and evidence‐based practice training in Spanish nursing students: A multicentre cross‐sectional study

Abstract: Aims and objectives To evaluate the commitment and level of self‐perceived training in evidence‐based practice among students of the Nursing degree of five Spanish universities. Background In university Health Sciences degrees, evidence‐based clinical practice can directly or indirectly impact the quality of care, the cost of the service provided and the safety of clinical practice. Design Multicentre cross‐sectional observational study according to STROBE guidelines. Methods The evidence‐based skills in Pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…(4) e period of literature is within the range of nearly 20 years. (5) e original clinical data are complete. (6) ere is no error in the operation steps during the study.…”
Section: Literature Search and Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…(4) e period of literature is within the range of nearly 20 years. (5) e original clinical data are complete. (6) ere is no error in the operation steps during the study.…”
Section: Literature Search and Literaturementioning
confidence: 99%
“…At the time of the basis, its core is to emphasize the evidence [3,4]. In order to obtain the best evidence to help ischemic stroke sufferers enhance their quality of life, some studies have pointed out that evidence-based ministration has a good intervention effect in the therapy of stroke sufferers, but its examination on pressure ulcers and prognosis of stroke sufferers are still in the exploratory stage [5]. In order to further explore the effect of evidence-based ministration intervention in stroke sufferers, this examination searched for and collected 8 randomized controlled studies, meta-analysis, combined with routine treatment and evidence-based treatment to intervene stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that clinical simulations help the students to increase their levels of confidence and satisfaction, allowing them to face real scenarios in the clinical practice. Other studies have justified the importance of commitment, perception and practical training based on the evidence on Spanish nursing students [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of these three pillars is vital to decision-making in the delivery of nursing care (Den Hertog & Niessen, 2021). The use of EBP in clinical practice settings has a positive impact on health care and is considered key to measuring quality in health care (Gómez-Salgado et al, 2023). In this respect, the World Health Organization (WHO) states that it is mandatory to incorporate the best evidence into the health services and care provided (World Health Organization, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The studies mentioned above also reveal barriers and enablers to the incorporation of EBP. The main barriers are lack of time, lack of incentive from management, resistance from leadership, lack of training, organizational culture, lack of competence to critically analyze scientific results, difficulty in carrying out research steps, lack of resources, and high workload (Gómez-Salgado et al, 2023;Lai et al, 2022). Camargo et al (2018) present as enablers the existence of an organizational culture that fosters EBP, institutional support / awareness, postgraduate training, the incorporation of course units on EBP in the undergraduate nursing degree, and the partnership between teachers, researchers, and nurses who are active in clinical practice.…”
Section: Introductionmentioning
confidence: 99%